Regional and Local Development in Times of Polarisation Re-thinking Spatial Policies in Europe - Lang, Thilo; Görmar, Franziska; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Despite the emphasis of the European Regional Policy on territorial cohesion, regional disparities have been increasing within Europe in the past years. The metropolitan areas in almost all countries are considerably growing while regions outside of agglomerations are stagnating or even declining. Against this background this book aims to provide an understanding of the underlying processes of polarisation and related regional and local policies. This open access volume contributes to the debates about polarisation and regional development by focussing on questions of spatial justice, power distribution and policy transfer. Theoretical and empirically grounded contributions show that European policies are indeed reproducing socio-spatial inequalities instead of challenging them. The book shows further the existing potentials and limits of individuals, economic, political and civil society actors to respond to polarisation on the regional and local level. In this book conceptual thoughts on polarisation, regional policy and regional development are combined with empirical research and resulting implications for policymaking. As such, it is a valuable source for early career students and researchers as well as professionals in the field of regional and economic development, policy consultants, and policy makers.
List of Illustrations -- Acknowledgements -- Notes on Contributors -- 1 Re-thinking Regional and Local Policies in Times of Polarisation: An Introduction -- PART I: SOCIO-SPATIAL POLARISATION IN THE EU AND QUESTIONS OF POWER -- 2 Geographical Uneven Development and Regional Futures: A Conversation -- 3 "New" Questions of Peripherality in Europe or How Neoliberal Austerity Contradicts Socio-spatial Cohesion -- 4 State Power, Spatial Inequality, and Geographical Expertise: Notes on Method -- PART II: REGIONAL AND COHESION POLICIES (RE-)PRODUCING SOCIO-SPATIAL DISPARITIES -- 5 Re-conceptualising Territorial Cohesion Through the Prism of Spatial Justice: Critical Perspectives on Academic and Policy Discourses -- 6 Questioning the Convergence of Cohesion and Innovation Policies in Central and Eastern Europe -- 7 Divergent Paths to Cohesion: The (Unintended) Consequences of a Place-Based Cohesion Policy -- 8 Urban Growth Pole Policy and Regional Development: Old Wine in New Bottles? -- 9 ReproducingSocio-spatial Unevenness through the Institutional Logic of Dual Housing Policies in Hungary -- PART III: RESPONSES TO REGIONAL POLARISATION AND ALTERNATIVE PERSPECTIVES -- 10 Out-Migration from Peripheries - How Cumulated Individual Strategies Affect Local Development Capacities -- 11 Towards a Progressive Local Development Approach - Insights from Local Community Initiatives in Hungary and Romania -- 12 Bypassing Structural Shortcomings: Innovative Firms in Peripheral Regions -- 13 Leading through Image Making? On the Limits of Emphasising Agency in Structurally Disadvantaged Rural Places -- PART IV: CONCLUSIONS: ABOUT THE RELEVANCE OF SCIENTIFIC RESEARCH FOR POLITICAL PRACTICE AND POLICY MAKING -- 14 Translating Scientific Results: Encouraging Reflective Policies as a Chance for Change -- 15 Understanding and Going beyond the Regional Policy Paradox: Conceptual Contributions to Studying Socio-spatial Polarisation in Europe.
Keywords: Human geography; Sociology, Urban; Ethnology; Culture; Europe -- Politics and government; Human Geography; Urban Sociology; Regional Cultural Studies; European Politics